THE EFFECT OF MENIRAN EXTRACT AS AN IMUNOSTIMULATOR ON THE INCREASE OF NEWCASTLE DISEASE ANTIBODY TITER IN BROILERS - Muhammad Evan Malik; Ida Bagus Kade Suardana; Samsuri; Ni Luh Eka Setiasih; I Made Kardena; Tjokorda Sari Nindhia (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Meniran is known as an herbal plant with potential as a natural immunostimulator due to its content of flavonoids, saponins, and tannins. These compounds help boost the immune response by stimulating cytokine production, accelerating immune cell activation, and increasing antibody production. Newcastle Disease (ND) is an infectious disease that frequently affects broilers and causes significant economic losses. Vaccination is the primary method for preventing ND; however, its effectiveness can vary depending on the immune response of the chickens. This study aims to evaluate the effect of meniran extract as an immunostimulant on increasing Newcastle Disease antibody titers in booster-vaccinated broilers. This study used a Completely Randomized Design with 30 Lohman MB 202 broilers divided into three treatment groups. The negative control group (K-) received neither vaccination nor meniran extract, the positive control group (K+) received only the ND La Sota booster vaccine, and the treatment group (P) received both the ND La Sota booster vaccine and meniran extract for 14 days before vaccination. Antibody titers were measured using the Hemagglutination Inhibition (HI) test on days 17, 25, and 32. Data were analyzed using ANOVA and regression analysis. The results showed that the administration of meniran extract significantly increased antibody titers (P<0.05), with mean values of 2.7, 4.1, and 6.0 (HI log 2), and an overall mean of 4.27. Regression analysis indicated that the treatment group (P) experienced a higher increase in antibody titers compared to the control groups, with the peak immune response occurring in the third week post-vaccination. The conclusion of this study is that meniran extract can act as a natural immunostimulant that enhances the effectiveness of the ND vaccine in broiler chickens. Therefore, further research with different doses and administration durations is needed to optimize its benefits.